Phytohormone signalling and cross-talk to alleviate aluminium toxicity in plants - Ranjan, Alok; Sinha, Ragini; Lal, Shambhu Krishan; Bishi, Sujit Kumar; Singh, Anil Kumar (Plant cell reports, 2021)
Aluminium (Al) is one of the most abundant metals in earth crust, which becomes toxic to the plants growing in acidic soil. Phytohormones like ethylene, auxin, cytokinin, abscisic acid, jasmonic acid and gibberellic acid are known to play important role in regulating Al toxicity tolerance in plants. Exogenous applications of auxin, cytokinin and abscisic acid have shown significant effect on Al-induced root growth inhibition. Moreover, ethylene and cytokinin act synergistically with auxin in responding against Al toxicity. A number of studies showed that phytohormones play vital roles in controlling root responses to Al toxicity by modulating reactive oxygen species (ROS) signalling, cell wall modifications, organic acid exudation from roots and expression of Al responsive genes and transcription factors. This review provides a summary of recent studies related to involvement of phytohormone signalling and cross-talk with other pathways in regulating response against Al toxicity in plants.